Assistance in Online Sexual Violence Cases for Women at SPEK-HAM Solo - Denny Hartanto; Marisa Kurnianingsih; Yoesoef Moestofa (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of this writing is to find out how to assist and what obstacles there are when assisting victims of online sexual violence at SPEK HAM Solo.It is hoped that this research can increase awareness of victims of violence to report perpetrators to the authorities and provide a deterrent effect for perpetrators so that they do not misuse the internet as a medium for sexual violence against women.Violence against women is a very serious and concerning problem in society. Violence can be physical, sexual, emotional, economic, and so on.This research uses empirical legal research methods or field research to collect empirical data directly from the field. This research is juridical-empirical and field type, where the author conducts research directly at the location to collect data. This research is a type of empirical research because it describes in detail and in depth a situation or phenomenon of the research object by developing concepts and collecting existing data. Data analysis in this research uses qualitative methods by collecting, grouping and selecting data from field studies and literature studies. Data is processed and compiled to draw conclusions in accordance with regulations, theories, principles and legal rules.Online sexual violence experienced by women in the city of Solo is a complex problem.